1989
DOI: 10.1164/ajrccm/140.2.340
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Deep Inhalation on Maximal Expiratory Flow during Intensive Treatment of Spontaneous Asthmatic Episodes

Abstract: Asthmatic patients who came to hospital for treatment of severe attacks were assessed for level of obstruction and the effects of a deep inhalation (DI) on degree of obstruction at various stages of their treatment and after recovery over several days. The more severe the obstruction, the greater was the constrictor effect of a DI; as lung function improved with intensive treatment, including corticosteroids, the constrictor effect diminished. Thus, we believe the constrictor effects of a DI relate to the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 9 publications
0
51
0
Order By: Relevance
“…At least three possible answers are presented in the literature. The first is provided by BURNS et al [17], PICHURKO et al [39], LIM and co-workers [40,41] and PLISS et al [42], which is based on the concept of relative hysteresis of airway versus lung and first developed by FROEB and MEAD [43]. They found, as did FISH et al [16], that in asthmatics, not only did deep inspiration fail to reverse spontaneous obstruction, it sometimes resulted in worsening of airway narrowing.…”
Section: Evidence Of Asm Involvement In Asthmamentioning
confidence: 99%
See 2 more Smart Citations
“…At least three possible answers are presented in the literature. The first is provided by BURNS et al [17], PICHURKO et al [39], LIM and co-workers [40,41] and PLISS et al [42], which is based on the concept of relative hysteresis of airway versus lung and first developed by FROEB and MEAD [43]. They found, as did FISH et al [16], that in asthmatics, not only did deep inspiration fail to reverse spontaneous obstruction, it sometimes resulted in worsening of airway narrowing.…”
Section: Evidence Of Asm Involvement In Asthmamentioning
confidence: 99%
“…They found, as did FISH et al [16], that in asthmatics, not only did deep inspiration fail to reverse spontaneous obstruction, it sometimes resulted in worsening of airway narrowing. Furthermore, LIM and co-workers [40,41] showed that the degree of bronchoconstriction induced by deep inspiration was related to the severity of spontaneous obstruction at the time of testing. That is, asthmatic subjects with severe spontaneous airway obstruction responded to deep inspiration with a further decrement in maximal expiratory flow (on maximal as opposed to partial expiratory flow-volume curves).…”
Section: Evidence Of Asm Involvement In Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported bronchodilation and a bronchoprotective effect of deep inspiration on the airways, which was absent or diminished in asthma (26). Indeed, in asthmatics, deep inspiration fails to reverse spontaneous obstruction, and sometimes even results in worsening of airway narrowing (27)(28)(29). Furthermore, the degree of bronchoconstriction induced by deep inspiration is related to spontaneous obstruction severity (28,29).…”
Section: Bronchial Hyperresponsivenessmentioning
confidence: 99%
“…Indeed, in asthmatics, deep inspiration fails to reverse spontaneous obstruction, and sometimes even results in worsening of airway narrowing (27)(28)(29). Furthermore, the degree of bronchoconstriction induced by deep inspiration is related to spontaneous obstruction severity (28,29).…”
Section: Bronchial Hyperresponsivenessmentioning
confidence: 99%